Live in Relationship in India: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The live in relationship is an arrangement in which two people decided to live together under the same roof without getting married. It’s a conduct of long –term relationship which is similar to marriage. The term live in relationship is the kind of relationship which is free from commitments and responsibilities unlikely traditional marriage. It is not recognized by the Hindu marriage Act, 1955 or by any other statutory law. The supreme court of India recognized live in relationship as legal relationship and is not considered as prohibited relationship.